The genesis of modern management : - Pollard, Sidney (E. Arnold, 1969)
Studies of the industrial revolution often ignore the problems of the management of large works - these were new, since earlier examples of controlling large numbers of men, such as armies of the builders of the pyramids, did not have to show a profit. The main problems are seen to have occurred in the management of labour, and in the construction of account which would help arrive at correct decisions